Selection of high yielding Jatropha curcas L. accessions for elite hybrid seed production - Nurul Hidayah Che Mat,; Md Atiqur Rahman Bhuiyan,; Siju Senan,; Zahira Yaakob,; Wickneswari Ratnam, (Universiti Kebangsaan Malaysia, 2015)
Phenotypic selection of individuals is the first step in a selective breeding program for elite hybrid seed production. In this study, a total of 295 Jatropha curcas individuals raised from cuttings representing 21 accessions, collected from eight different countries were evaluated for growth performance. The evaluation was done at the Biodiesel Research Station of Universiti Kebangsaan Malaysia, Kuala Pilah from December 2012 to December 2013. Individual plants from each accession were observed on several agronomic and yield related traits and all the data were recorded periodically. Performance of each accession was analyzed using Statistical Analysis System (SAS) 9.4. Four traits which were plant height (PH), number of flowers per inflorescence (NFI), number of female flowers per inflorescence (NFFPI) and hundred seed weight (HSW) showed significant differences among the accessions after one year of planting. Maximum values for each trait were 115.5 cm for PH, 6 for number of branches per plant (BPP), 9 for number of inflorescences per plant (NIPP), 25 for number of fruits per plant (NFPP), 5 for number of fruits per inflorescence (NFPI), 191 for NFI, 10 for NFFPI, 81.0 g for HSW and 70 for number of seeds per plant (NSPP). Accession number 1 from Thailand showed the best performance for most traits. A highly significant and positive correlation was found between NFPP and NSPP. Based on superior trait values for NIPP, NFPP, NFPI, NFI, NFFPI and HSW, five plants from accession UKMJC 01, 04, 05, 13 and 14 have been selected for generating elite intraspecific hybrids.